Advanced issues in the green economy and sustainable development in emerging market economies - Popkova, Elena G. (Cambridge : Cambridge University Press, 2022)
This Element goes far beyond economic theory. It will also be of interest to representatives of the environmental sciences due to its focus on the "green" economy and sustainable development. It will also be interesting to the representatives of the social sciences, as it takes into account the peculiarities of emerging market economies. Learning from the COVID-19 pandemic makes this Element interesting from a health economics perspective.
Title from publisher's bibliographic system (viewed on 24 Mar 2022).
Keywords: Sustainable development -- Developing countries; Environmental economics -- Developing countries